2020
DOI: 10.1021/acsomega.0c01581
|View full text |Cite
|
Sign up to set email alerts
|

In Silico ADME/Tox Profiling of Natural Products: A Focus on BIOFACQUIM

Abstract: Natural products continue to be major sources of bioactive compounds and drug candidates not only because of their unique chemical structures but also because of their overall favorable metabolism and pharmacokinetic properties. The number of publicly accessible natural product databases has increased significantly in the past few years. However, the systematic ADME/ Tox profile has been reported on a limited basis. For instance, BIOFACQUIM was recently published as a public database of natural products from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 43 publications
0
83
0
Order By: Relevance
“…The blood–brain barrier (BBB) protects the central nervous system (CNS) preventing certain substances (mostly harmful) from entering the brain tissues. The BBB limits the passage of most of the external compounds to maintain CNS at a steady state (Durán-Iturbide et al, 2020 ; Miao et al, 2019 ). In addition, P-glycoprotein (P-gp) actively transports a wide variety of compounds out of cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood–brain barrier (BBB) protects the central nervous system (CNS) preventing certain substances (mostly harmful) from entering the brain tissues. The BBB limits the passage of most of the external compounds to maintain CNS at a steady state (Durán-Iturbide et al, 2020 ; Miao et al, 2019 ). In addition, P-glycoprotein (P-gp) actively transports a wide variety of compounds out of cells.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter has a direct impact in determining the dose regimen (how often) and dose size (how much) of a given drug. Thus, its prediction helps us to determine the feasibility of clinical dosing and provides a framework for the starting dose in in vivo studies (Durán-Iturbide et al, 2020 ). In this work, the TC values of 1,2,3-triazoles-phtalimide derivatives varied from −0.26 to 0.85 log (mL/min/kg), for H2 and E37 derivatives, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Authors of that work found that the absorption and distribution profile of compounds in BIOFACQUIM is similar to approved drugs, while the metabolism profile is comparable to other NP databases. The excretion profile of compounds in BIOFACQUIM is different from approved drugs, but their predicted toxicity profile is comparable [ 30 ].…”
Section: Chemoinformatic Profilingmentioning
confidence: 99%
“…Additionally, PSC-db allows for computing the correlation between any pair of the available features among a subset of compounds (physicochemical properties, lipophilicity, water solubility, pharmacokinetics and drug-likeness). Interestingly, these types of correlations have been reported, for example, to validate the estimations of the permeability of compounds [ 21 ], the estimations of oral absorption [ 22 ], and to compare the ADME/Tox profiling of several important chemical compound databases [ 23 ]. Nowadays, it is useful to have a repository that helps the users to find natural compounds with potentially similar properties/bioactivities.…”
Section: Introductionmentioning
confidence: 99%